Improving Documentation of and Access to Diabetic Retinopathy Screening at a Student-Run Free Clinic - Aleksandra Zarska; Sharmi Amin; Joshua R Ehrlich; Hari Conjeevaram (Journal of Student-Run Clinics, 2024)
Background: Diabetic retinopathy (DR) affects approximately 9.6 million people in the United States (US) and is the leading cause of vision loss in working-age adults. However, less than 50% of people with diabetes in the US undergo the recommended screening. We aimed to assess need for DR screening (DRS) at the University of Michigan Student-Run Free Clinic (UMSRFC) and examine current DRS documentation practices to inform quality improvement initiatives at the clinic.Methods: We conducted a needs-assessment survey of 67 patients to examine access to eye and vision care among patients seen at the UMSRFC between January and April 2023. Descriptive analysis of survey data was performed. A retrospective chart review of all patients seen at the clinic between March 2021 and March 2023 was conducted to evaluate documentation of DRS in the medical record. These results informed the development of a DRS initiative at the clinic.Results: Of the 67 patients surveyed, 17 had a diagnosis of diabetes. Twenty-six patients reported an eye problem, of which 16 (62.0%) reported blurry vision, 9 (35.0%) reported floaters, and 1 (4.0%) reported dark/empty areas in their vision. Chart review yielded 404 patients, of which 70 had a diagnosis of type 2 diabetes. Twenty-eight (40.0%) had any mention of a diabetic eye exam in their chart, and 12 of these were up to date with the American Diabetes Association (ADA) screening guidelines. Twenty-three (33.0%) patients had any mention of a referral to an optometrist or ophthalmologist in their chart. On the DRS day, three patients were screened for DR. No cases of DR were identified.Conclusion: Survey and chart review data indicated a need for increased DRS and improved documentation practices of DRS at the UMSRFC. A DRS initiative was successfully implemented at the UMSRFC under the oversight of an ophthalmologist.